The Supreme Court - Baum, Lawrence (Washington, D.C. : CQ Press, 2010)
The court -- The justices -- The cases -- Decision making -- Policy outputs -- The court's impact.
Includes bibliographical references and indexes.
Keywords: United States. -- Supreme Court; Constitutional law -- United States; Courts of last resort -- United States; Judicial review -- United States